Narrating Karma and Rebirth: Buddhist and Jain Multi-life Stories, by Naomi Appleton. - Barker, Sophie (Buddhist Studies Review, 2017)
Narrating Karma and Rebirth: Buddhist and Jain Multi-life Stories, by Naomi Appleton. Cambridge University Press, 2014. 244pp. Hb. £67.00; Pb. £23.99. ISBN-13: 978-1107566142.